Role of myeloid early endothelial progenitor cells in bone formation and osteoclast differentiation in tissue construct based on hydroxyapatite poly(ester‐urethane) scaffolds. Issue 11 (14th March 2016) - Shi, Yang; Wang, Fanlu; Tiwari, Sanjay; Yesilbas, Meran; Steubesand, Nadine; Weitkamp, Jan‐Tobias; Klüter, Tim; Lippross, Sebastian; Eglin, David; Seekamp, Andreas; Fuchs, Sabine
ABSTRACT: Engineering of a vascularized bone construct is a highly challenging task which needs to take into account the impact of different components on the bone regeneration process. Bone repair influencing factors in such constructs range from the material properties and scaffold design, to the interaction of different cell types contributing to bone formation and remodeling or neovascularization, respectively. In this context, early endothelial progenitor cells (EPC), mononuclear cells isolated from the peripheral blood, express the endothelial marker CD31 but also a series of myeloid markers and have been shown to support the formation of vessel‐like structures. These cells are also characterized by a highly adaptable phenotype influenced by other cells creating an instructive niche. The present study was designed to investigate the impact of EPC on bone formation or remodeling using a co‐culture system of outgrowth endothelial cells, mature endothelial cells isolated from the peripheral blood cell cultures, and mesenchymal stem cells grown on hydroxyapatite poly(ester‐urethane) scaffolds. The formation of vessel‐like structures in these constructs was shown by CLSM and immunohistochemistry and further evaluated by real time RT‐PCR. Osteogenic differentiation in these constructs was investigated by von Kossa, Alizarin Red, and real time PCR. Data indicated that osteogenic differentiation occurred within the constructs after 14 days of culture but without a direct influence by EPC in this process. Finally, although we observed a series of osteoclast related makers in the constructs when EPC were included, no indications for an increased osteoclast‐like activity, which might lead to increased bone resorption, were observed. © 2016 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 34:1922–1932, 2016.